2021
DOI: 10.3389/fpubh.2021.774237
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Myopia and Other Risk Factors With Anxiety and Depression Among Chinese University Freshmen During the COVID-19 Pandemic

Abstract: Purpose: To investigate the association of myopia and other risk factors with anxiety and depression among Chinese university freshmen during the coronavirus disease 2019 (COVID-19) pandemic.Methods: This cross-sectional study was conducted at the Tianjin Medical University from October 2020 to December 2020. Ophthalmic examination of the eyes was performed by an experienced ophthalmologist. Detailed information on depression, anxiety, and other risk factors was collected via the Self-rating Anxiety Scale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Depending on the chronicity of the ocular condition, studied levels of anxiety could change. Thus, ocular chronic conditions, such as myopia or pseudo myopia, were associated with anxiety [ 30 , 31 ]. While other ocular pathologies, such as uveitis, showed changes in state anxiety [ 32 ] instead of in trait anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the chronicity of the ocular condition, studied levels of anxiety could change. Thus, ocular chronic conditions, such as myopia or pseudo myopia, were associated with anxiety [ 30 , 31 ]. While other ocular pathologies, such as uveitis, showed changes in state anxiety [ 32 ] instead of in trait anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of social isolation, the reason for the limitations of their living environment, and the pressure from online learning, they are more likely to suffer from mental health problems ( 3 , 4 ), including anxiety, depression, and insomnia. Zhang et al ( 5 ) reported that the prevalence rates of anxiety and depression among Chinese college students were 10.3 and 25.1% during the COVID-19 pandemic, respectively. Additionally, research evidence showed that 16.9% of students once suffered insomnia in varying degrees during the pandemic ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, it is hard to fully include all potential factors that may influence the incidence of depression and anxiety. The absence of these factors, such as refractive error (50,51) and menopausal women (52,53), may affect the evaluation of the effect value. Despite these limitations, this is the first report to expressly point out which patients with CDDD are susceptible to depression and anxiety based on the cross-sectional case-control study design.…”
Section: Discussionmentioning
confidence: 99%